2019
DOI: 10.1111/acem.13900
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Traumatic Aortic Injury in the Pan‐scan Era

Abstract: Background: In the era of frequent head-to-pelvis computed tomography (CT) for adult blunt trauma evaluation, we sought to update teachings regarding aortic injury by determining 1) the incidence of aortic injury; 2) the proportion of patients with isolated aortic injury (without other concomitant thoracic injury); 3) the clinical implications of aortic injury (hospital mortality, length of stay [LOS], and rate of surgical interventions); and 4) the screening value of traditional risk factors/markers (such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…An investigation that enrolled 24,010 BTAI patients reported that most patients had chest injury, with rib fractures and pulmonary contusion occurring most frequently. [12] In a nationwide case series, Sheehan et al [13] discovered that rib fractures, spine fractures, a nd trunk abrasion were risk factors for blunt abdominal aortic injury (BAAI). Moreover, previous research has found that MVAs are a common cause of traumatic aortic injury.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation that enrolled 24,010 BTAI patients reported that most patients had chest injury, with rib fractures and pulmonary contusion occurring most frequently. [12] In a nationwide case series, Sheehan et al [13] discovered that rib fractures, spine fractures, a nd trunk abrasion were risk factors for blunt abdominal aortic injury (BAAI). Moreover, previous research has found that MVAs are a common cause of traumatic aortic injury.…”
Section: Discussionmentioning
confidence: 99%
“…BTAI is a clinically rare but fatal condition ( 17 ). RFs serve as a chief risk factor for BTAI ( 18 , 19 ). The retrospective study by Choi et al showed that RFs contributed to approximately 22.9% of all closed TAI cases ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular injury is diagnosed by CTA scan imaging, as the classic findings of widened mediastinum and hemopneumothorax on a screening CXR are not sensitive [17]. Inaba et al [18] identified 3 types of aortic disruptionhemodynamically unstable full thickness laceration, symptomatic intimal dissection with occlusion, and asymptomatic intimal dissection without occlusion.…”
Section: Discussionmentioning
confidence: 99%